2000
DOI: 10.1038/sj.ijo.0801436
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the obese child: adequacy of the body mass index for clinical practice and epidemiology

Abstract: OBJECTIVE: To assess the ability of simple de®nitions of BMI to successfully screen for children with high body fatness. DESIGN: We determined the sensitivity and speci®city of the body mass index (BMI) by testing its ability to correctly identify children with high body fat percentage. Receiver operator characteristic (ROC) analyses were carried out using the top 5% of body fat percentage to de®ne children as obese (true positives). SUBJECTS: Representative sample of 4175 7 y-old (88 ± 92 month-old) children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
201
4
14

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(231 citation statements)
references
References 19 publications
12
201
4
14
Order By: Relevance
“…11 Diagnostic accuracy of national and 'international' obesity definitions Diagnostic accuracy of BMI for age depends on whether it is defined relative to national BMI reference data, or to the 'international' or 'IOTF' definitions of paediatric overweight and obesity. 12 Four published studies [13][14][15][16] have now made a direct comparison of the diagnostic ability of cutoffs based on national reference data (from the US, UK, and Singapore) with those recommended by the IOTF. All four found that the sensitivity of the IOTF obesity definition was much lower than that of definitions based on national reference data (such as BMI X95th percentile).…”
Section: Evidence Base On Diagnostic Accuracymentioning
confidence: 99%
See 2 more Smart Citations
“…11 Diagnostic accuracy of national and 'international' obesity definitions Diagnostic accuracy of BMI for age depends on whether it is defined relative to national BMI reference data, or to the 'international' or 'IOTF' definitions of paediatric overweight and obesity. 12 Four published studies [13][14][15][16] have now made a direct comparison of the diagnostic ability of cutoffs based on national reference data (from the US, UK, and Singapore) with those recommended by the IOTF. All four found that the sensitivity of the IOTF obesity definition was much lower than that of definitions based on national reference data (such as BMI X95th percentile).…”
Section: Evidence Base On Diagnostic Accuracymentioning
confidence: 99%
“…Up to 40-50% of the fattest children were not identified as obese by the IOTF approach. [13][14][15][16] These studies also reported that the sensitivity of the IOTF definition was highly sex-specific. In the UK, for example, use of the IOTF approach has much lower sensitivity in boys than girls, 13 leading to the erroneous conclusion that obesity is more prevalent in girls than boys.…”
Section: Evidence Base On Diagnostic Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…It prepared BMI percentiles from databases of six countries with low prevalence of overweight and obtained the percentile corresponding to a BMI of 25 kg/m 2 for different age groups and both genders. In general, compared to other references, WHO's standards produce similar estimates of overweight but lower estimates of obesity (Reilly et al, 2000;Kain et al, 2002;Abrantes et al, 2003). Chilean investigators have developed local percentiles of BMI for age and have proposed the use of percentiles based not on age but on Tanner stage (Burrows and Muzzo, 1999;Burrows, 2001).…”
Section: Mexican Anthropometric Percentiles In Adolescentsmentioning
confidence: 99%
“…Estimates of the prevalence of overweight and obesity in population groups are typically based on body mass index (BMI), and BMI centile curves have been developed for use in the paediatric population for clinical and possibly epidemiological purposes (Cole et al, 1995). It has been suggested, however, that BMI may be a less sensitive indicator of fatness amongst children (Reilly et al, 2000), and BMI gives no indication about fat distribution. Until more studies include ethnic groups other than whites however, BMI should be used cautiously in assessing fatness across populations (Dietz & Bellizzi, 1999).…”
Section: Introductionmentioning
confidence: 99%